On the biology of the alien Red Sea goatfish, Parupeneus forsskali (Fourmanoir & Guézé, 1976) in the Aegean Sea, eastern Mediterranean - Georgios Vagenas; Aikaterini Dogrammatzi; Gerasimos Kondylatos; Paraskevi K. Karachle (Marine Biology Research, 2023)

Filling in data gaps on the phaeton dragonet [ Synchiropus phaeton (Günther, 1861)]: a study on biological characteristics in the eastern Mediterranean (Aegean Sea, Greece) - Georgios Vagenas; Charis Apostolidis; Aikaterini Dogrammatzi; Paraskevi K. Karachle (Marine Biology Research, 2021)

Age, growth and feeding habits of boarfish ( Capros aper ) in the Aegean and Ionian Seas (Greece) - Georgios Vagenas; Paraskevi K. Karachle; Aikaterini Dogrammatzi; Athanassios C. Tsikliras (Marine Biology Research, 2020)

“New Mediterranean Biodiversity Records” (March 2017) - L. LIPEJ; I. ACEVEDO; E.H.K. AKEL; A. ANASTASOPOULOU; A. ANGELIDIS; E. AZZURRO; L. CASTRIOTA; M. ÇELIK; L. CILENTI; F. CROCETTA; A. DEIDUN; A. DOGRAMMATZI; et al. (Mediterranean Marine Science, 2017)
This Collective Article presents information on 22 species belonging to 5 Phyla, arranged geographically from from west to east. The new records were found in 8 countries as follows: Spain: first record of the two scarcely known nemerteans Baseodiscus delineatus and Notospermus geniculatus in Formentera; Malta: second record of the alien fish Lagocephalus sceleratus; Italy: the alien polychaete Syllis pectinans and the isopod Paranthura japonica, as well as the cryptogenic opisthobranch Anteaeolidiella lurana, were found in the fouling assemblages along the docks of the port of Livorno. New decapod records are reported from Sicily (the alien Callinectes sapidus and the native Pachygrapsus maurus) and Apulia (Percnon gibbosus and Procambarus clarkii); the lesser amberjack Seriola fasciata extended its geographical range to the Egadi Isands and Siganus luridus was documented for the first time along the Ionian coasts of Apulia and Calabria. Slovenia: the first record of the alien bivalve Brachidontes pharaonis is reported, together with a survey of up to date Adriatic records. Greece: the first record of the gastropod Rhinoclavis kochi is reported from Gavdos island. In addition, two records of endangered and rare cartilaginous fish were reported, namely, the shark Hexanchus griseus and the ray Leucoraja fullonica, as well as additional records of Siganus luridus for Lesvos and Malleus regula and Fulvia fragilis from Astypalaia. Turkey: the black wing flyingfish Hirundichthys rondeletii is reported for the very first time from the Black Sea. Egypt: the Indo-Pacific crab Halimede ochtodes is reported as established in Port Said. In addition, biometric parameters and meristic counts are reported for Anthias anthias in Damietta. Cyprus: the alien opisthobranch gastropod Bursatella leachii is reported for first time.

New Mediterranean Biodiversity Records (March 2016) - P. K. KARACHLE; A. ANGELIDIS; G. APOSTOLOPOULOS; D. AYAS; M. BALLESTEROS; C. BONNICI; M. M. BRODERSEN; L. CASTRIOTA; N. CHALARI; J. M. COTTALORDA; F. CROCETTA; A. DEIDUN; et al. (Mediterranean Marine Science, 2016)
In this Collective Article on “New Mediterranean Biodiversity Records”, we present additional records of species found in the Mediterranean Sea. These records refer to eight different countries throughout the northern part of the basin, and include 28 species, belonging to five phyla. The findings per country include the following species: Spain: Callinectes sapidus and Chelidonura fulvipunctata; Monaco: Aplysia dactylomela; Italy: Charybdis (Charybdis) feriata, Carcharodon carcharias, Seriola fasciata, and Siganus rivulatus; Malta: Pomacanthus asfur; Croatia: Lagocephalus sceleratus and Pomadasys incisus; Montenegro: Lagocephalus sceleratus; Greece: Amathia (Zoobotryon) verticillata, Atys cf. macandrewii, Cerithium scabridum, Chama pacifica, Dendostrea cf. folium, Ergalatax junionae, Septifer cumingii, Syphonota geographica, Syrnola fasciata, Oxyurichthys petersi, Scarus ghobban, Scorpaena maderensis, Solea aegyptiaca and Upeneus pori; Turkey: Lobotes surinamensis, Ruvettus pretiosus and Ophiocten abyssicolum. In the current article, the presence of Taractes rubescens (Jordan & Evermann, 1887) is recorded for the first time in the Mediterranean from Italy. The great contribution of citizen scientists in monitoring biodiversity records is reflected herein, as 10% of the authors are citizen scientists, and contributed 37.5% of the new findings.

New Mediterranean Biodiversity Records (April 2015) - Α. ΖΕΝΕΤΟΣ; E.H.KH. AKEL; C. APOSTOLIDIS; M. BILECENOGLU; G. BITAR; V. BUCHET; N. CHALARI; M. CORSINI-FOKA; F. CROCETTA; A. DOGRAMMATZI; M. DRAKULIĆ; G. FANELLI; et al. (Mediterranean Marine Science, 2015)
The Collective Article ‘New Mediterranean Biodiversity Records’ of the Mediterranean Marine Science journal offers the means to publish biodiversity records in the Mediterranean Sea. The current article is divided in two parts, for records of native and alien species respectively. The new records of native fish species include: the slender sunfish Ranzania laevis and the scalloped ribbonfish Zu cristatus in Calabria; the Azores rockling Gaidropsarus granti in Calabria and Sicily; the agujon needlefish Tylosurus acus imperialis in the Northern Aegean; and the amphibious behaviour of Gouania willdenowi in Southern Turkey. As regards molluscs, the interesting findings include Ischnochiton usticensis in Calabria and Thordisa filix in the bay of Piran (Slovenia). The stomatopod Parasquilla ferussaci was collected from Lesvos island (Greece); the isopod Anilocra frontalis was observed parasitizing the alien Pteragogus trispilus in the Rhodes area. The asteroid Tethyaster subinermis and the butterfly ray Gymnura altavela were reported from several localities in the Greek Ionian and Aegean Seas. The new records of alien species include: the antenna codlet Bregmaceros atlanticus in Saronikos Gulf; three new fish records and two decapods from Egypt; the establishment of the two spot cardinal fish Cheilodipterus novemstriatus and the first record of the Indo-Pacific marble shrimp Saron marmoratus in semi-dark caves along the Lebanese coastline; the finding of Lagocephalus sceleratus, Sargocentron rubrum, Fistularia commersonii and Stephanolepis diaspros around Lipsi island (Aegean Sea, Greece); the decapod Penaeus hathor in Aegean waters; the decapod Penaeus aztecus and the nudibranch Melibe viridis in the Dodecanese islands; the finding of Pinctada imbricata radiata in the Mar Grande of Taranto (Ionian Sea, Italy) and the Maliakos Gulf (Greece).

New Mediterranean Marine biodiversity records (June 2013) - I. SIOKOU; A.S. ATES; D. AYAS; J. BEN SOUISSI; T. CHATTERJEE; M. DIMIZA; H. DURGHAM; K. DOGRAMMATZI; D. ERGUDEN; V. GERAKARIS; M. GREGO; Y. ISSARIS; et al. (Mediterranean Marine Science, 2013)
This paper concerns records of species that have extended their distribution in the Mediterranean Sea. The finding of the rare brackish angiosperm Althenia filiformis in the island of Cyprus is interesting since its insertion in the Red Data Book of the Flora of Cyprus is suggested. The following species enriched the flora or fauna lists of the relevant countries: the red alga Sebdenia dichotoma (Greece), the hydrachnid mite Pontarachna adriatica (Slovenia), and the thalassinid Gebiacantha talismani (Turkey). Several alien species were recorded in new Mediterranean localities. The record of the burrowing goby Trypauchen vagina in the North Levantine Sea (Turkish coast), suggests the start of spreading of this Lessepsian immigrant in the Mediterranean Sea. The findings of the following species indicate the extension of their occurrence in the Mediterranean Sea: the foraminifer Amphistegina lobifera (island of Zakynthos, Greece), the medusa Cassiopea andromeda (Syria), the copepod Centropages furcatus (Aegean Sea), the decapod shrimp Melicertus hathor (island of Kastellorizo, Greece), the crab Menoethius monoceros (Gulf of Tunis), the barnacles Balanus trigonus, Megabalanus tintinnabulum, Megabalanus coccopoma and the bivalves Chama asperella, Cucurbitula cymbium (Saronikos Gulf, Greece).